Memoryscape to future: conserving heritage of Sungai Buloh Leprosy Settlement / Mirrah Atika Che Abdullah - Che Abdullah, Mirrah Atika (2017)
Heritage is a unique character of the identity, which is very high value and have significant element. The treatment of preservation and conservation of heritage are one of way to keep protecting the historical of the heritage would not be neglected and lost. Sungai Bu/oh Leprosy Settlement was once be a second largest leprosy center in the world. However, nowadays the historical of the place almost be forgotten and less appreciation. The goal of this study is towards making a Sungai Bu/oh Leprosy Settlement as Traditional Alternative Medicine through traditional approach in order to enhance the functionality and improve the quality of life at Sungai Bu/oh. As based on the design concept of 'Rebirth The Spirit of Sungai Bu/oh Leprosy Settlement'; thus the proposed design is hoped to highlight the important values based on the significant element. Lastly, the final phase of this study will provide a design proposal which is important to make a guideline planning and design practice in this study. Thus the proposed design is hope to provide a guide to landscape architecture heritage by creating a sense of place towards enhancing and promoting the heritage of Sungai Bu/oh Leprosy Settlement.